Psychometric study of spanish version of aggression questionnaire Buss and Pe - Matalinares Calvet, María (2012)
The basic objective of this research was to conduct psychometric adaptation of the Spanish version of the Aggression Questionnaire (Buss and Perry, 1992; Andreu, Peña and Grana, 2002). It was worked with 3,632 from 10 to 16 years, of both sexes, of 1 º to 5 º degree of secondary education, fromdifferent educational institutions of the coast, highlands and jungle of Peru. This study analyzes the structure of the questionnaire through exploratory factor analysis evidencing the model proposed by Buss and determines acceptable internal consistency. The results obtained show an acceptable fit to the four-factor model, adequate internal consistency, scales percentile and interpretative rules.